Academic efficiency of engineering university degrees and its driving factors. A PLS-DEA approach (2022)
This research develops an academic production function for the educational process of industrial engineers in Colombia. The proposed function objectively analyses the relationships between the academic competencies obtained in secondary education and the university. The data used correspond to the standardized tests of 4,977 students at the end of high school and university. In the first stage of the model, the structure of the production function was empirically evaluated using a Partial Least Square-Structural Equation Modeling approach. Consequently, in the second stage, the efficiency of the relationships in the academic production function is estimated using Data Envelopment Analysis. The Goodness of Fit index of the empirical model was 0.89, thus, confirming the relationships between the construct's variables. The model validates four transformation relationships and subsequently estimates the efficiency of the interactions in the production function. The average efficiency results of the model in its constant scale are 16.30%, 2.17%, and 5.43%. In conclusion, the model explains the capacity of universities to transform inputs (basic competencies of the secondary school) into desired outputs (professional academic competencies). Additionally, the model analyses professional performance from the interactions among academic competencies. © Foundation of International Studies, 2022 and CSR, 2022.